(untitled) (Indian Journal of Animal Production and Management, 2026)
The research study aimed to explore the reasons for buffaloes experiencing anestrus during their breeding season in Basrah governorate, Iraq. The research included a sample of 52 buffaloes suffering from anestrus and another five in the estrus phase. The reproductive system of these animals was examined to evaluate the causes of anestrus using trans-rectal ultrasonography. Antioxidant enzymes, catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GSH-px), and the level of malondialdehyde (MDA) were measured in the blood of anestrus buffaloes and compared with those of normal cyclic buffaloes. Ultrasonographical results revealed that the infertile buffaloes suffered from ovarian inactivity, anovulatory follicles, persistent corpus luteum, and luteal cysts at rates of 34.16%, 21.15%, 17.30%, and 13.46%, respectively. The research found that 13.46% of buffaloes with normal estrous cycles experienced silent estrus. The results also showed a significant decrease (P<0.05) in CAT, SOD, and GSH-px in anestrus buffaloes compared with regularly cyclic buffaloes and a significant elevation (P<0.05) in the MDA level in anestrus buffaloes compared with the control group. The study concluded that the animals were under oxidative stress due to heat stress and a poor diet in highly productive buffaloes, which plays an important role in anestrus and infertility.